1986
DOI: 10.1037/0022-3514.50.4.744
|View full text |Cite
|
Sign up to set email alerts
|

Impact of couple patterns of problem solving on distress and nondistress in dating relationships.

Abstract: A theory of couple patterns of problem solving that involves the Rusbult and Zembrodt (1983) exitvoice-loyalty-neglect typology of problem-solving responses is advanced and tested in a sample of dating relationships. Destructive problem-solving responses (exit and neglect) were more powerfully predictive of couple distress/nondistress than were constructive problem-solving behaviors (voice and loyalty). Tendencies to react with voice to mild relationship problems were also signihcantly predictive of couple fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
142
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(155 citation statements)
references
References 34 publications
11
142
0
2
Order By: Relevance
“…As means of validating the constructive-destructive dimension, Rusbult, Johnson, and Morrow (1986) found that destructive behaviors lead to poor relationship outcomes whereas constructive behaviors lead to better relationship outcomes. However, because the present study does not include assessments of relationship functioning, we can only assume that these behaviors are constructive or destructive for relationships.…”
Section: Age and Reactivity To Interpersonal Tensionsmentioning
confidence: 99%
“…As means of validating the constructive-destructive dimension, Rusbult, Johnson, and Morrow (1986) found that destructive behaviors lead to poor relationship outcomes whereas constructive behaviors lead to better relationship outcomes. However, because the present study does not include assessments of relationship functioning, we can only assume that these behaviors are constructive or destructive for relationships.…”
Section: Age and Reactivity To Interpersonal Tensionsmentioning
confidence: 99%
“…More specifically, research shows that negative relationship events like conflict tend to have a larger impact than positive events (Gottman, 1994;see Baumeister, Bratslavsky, Finkenauer, & Vohs, 2001 for review), and conflict interactions are often used in lab-based studies of relationship functioning to infer relational health (e.g., Gottman, 1994;Levenson & Gottman, 1985;Overall, Fletcher, Simpson, & Sibley, 2009). Conflict can be detrimental to individual (Burman & Margolin, 1992;Umberson, Williams, Powers, Liu, & Needham, 2006) and relationship (Gottman & Levenson, 2000;Rusbult, Johnson, & Morrow, 1986) health when not handled effectively. Whether or not a conflict is destructive may partly depend upon its immediate emotional impact.…”
Section: Relational Conflict and Verification/enhancement Processesmentioning
confidence: 99%
“…Perhaps even more common than attractive alternatives, relationship conflict is a threat that many, if not all, couples experience. How individuals react to relationship conflict will influence the quality of the relationship (Rusbult, Johnson, & Morrow, 1986), as the more destructively a partner reacts, the less satisfied and committed the partners will be . Reacting in an accommodative, constructive fashion, on the other hand, has been shown to curb the spiral of negativity that often results from the "tit for tat" behaviour that characterizes couple conflict, and is predicted by commitment (Rusbult, Verette, Whitney, Slovik, & Lipkus, 1991) and self-regulatory strength (Finkel & Campbell, 2001).…”
Section: Relationship-specific Identification and Other Types Of Rmrsmentioning
confidence: 99%